Cancer Incidence in World Trade Center Rescue and Recovery Workers: 14 Years of Follow-Up. (9th September 2021) - Li, Jiehui; Yung, Janette; Qiao, Baozhen; Takemoto, Erin; Goldfarb, David G; Zeig-Owens, Rachel; Cone, James E; Brackbill, Robert M; Farfel, Mark R; Kahn, Amy R; Schymura, Maria J; Shapiro, Moshe Z; et al.
Abstract: Background: Statistically significantly increased cancer incidence has been reported from 3 cohorts of World Trade Center (WTC) disaster rescue and recovery workers. We pooled data across these cohorts to address ongoing public concerns regarding cancer risk 14 years after WTC exposure. Methods: From a combined deduplicated cohort of 69 102 WTC rescue and recovery workers, a sample of 57 402 workers enrolled before 2009 and followed through 2015 was studied. Invasive cancers diagnosed in 2002-2015 were identified from 13 state cancer registries. Standardized incidence ratios (SIRs) were used to assess cancer incidence. Adjusted hazard ratios (aHRs) were estimated from Cox regression to examine associations between WTC exposures and cancer risk. Results: Of the 3611 incident cancers identified, 3236 were reported as first-time primary (FP) cancers, with an accumulated 649 724 and 624 620 person-years of follow-up, respectively. Incidence for combined FP cancers was below expectation (SIR = 0.96, 95% confidence interval [CI] = 0.93 to 0.99). Statistically significantly elevated SIRs were observed for melanoma-skin (SIR = 1.43, 95% CI = 1.24 to 1.64), prostate (SIR = 1.19, 95% CI = 1.11 to 1.26), thyroid (SIR = 1.81, 95% CI = 1.57 to 2.09), and tonsil (SIR = 1.40, 95% CI = 1.00 to 1.91) cancer. Those arriving on September 11 had statistically significantly higher aHRs than those arriving after September 17, 2001, for prostate (aHR = 1.61, 95% CI = 1.33 to 1.95) and thyroid (aHR = 1.77, 95% CI = 1.11 to 2.81) cancers, with a statistically significant exposure-response trend for both. Conclusions: In the largest cohort of 9/11 rescue and recovery workers ever studied, overall cancer incidence was lower than expected, and intensity of WTC exposure was associated with increased risk for specific cancer sites, demonstrating the value of long-term follow-up studies after environmental disasters.